1994
DOI: 10.1111/j.1365-2249.1994.tb06515.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing and presentation of tetanus toxin by antigen-presenting cells from patients with chronic granulomatous disease (CGD) to human specific T cell clones are not impaired

Abstract: SUMMARYThe capacity of peripheral blood lymphocytes (PBL) or Epstein-Barr virus (EBV)-transformed B cell lines from CGD patients to process and present tetanus toxin (tt)-specific epitopes was assessed using various tt preparations and human tt-specific T cell clones. PBL from all ofthe donors were able to process and present either native tt and/or denatured tt to human T cell clones specific for various tt epitopes. Furthermore, no difference was found in the antigen requirement when normal or CGD EBV-B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[ 3 H]thymidine incorporation was measured in a ␤-counter (Top Count; Packard Bioscience S.A., Zürich, Switzerland). T-cell cloning (0.3 cell/well) was performed as described earlier (3,36). Clones with a stimulation index of Ͼ2 were further expanded and retested for specificity as described previously (4,36).…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 H]thymidine incorporation was measured in a ␤-counter (Top Count; Packard Bioscience S.A., Zürich, Switzerland). T-cell cloning (0.3 cell/well) was performed as described earlier (3,36). Clones with a stimulation index of Ͼ2 were further expanded and retested for specificity as described previously (4,36).…”
Section: Methodsmentioning
confidence: 99%
“…Presentation of exogenous ovalbumin but not tetanus toxoid Ag was altered in APC from CGD patients (7, 8). Neither study identified the defective oxidase subunits in the CGD patient-derived APC.…”
Section: Introductionmentioning
confidence: 99%
“…In phagocytes, nitric oxide production is required for processing bacterial polysaccharides into fragments capable of binding MHC-II for presentation to T cells (52). Conflicting reports with B lymphocytes also suggest roles for superoxide and NADPH oxidase in MHC-II presentation, yet these early studies employed samples from reported CGD patients without genetic analysis to confirm defective oxidase subunits (53, 54). Although B lymphocytes express functional NADPH oxidase subunits (55), the precise function of this enzyme complex in these cells remains unclear.…”
Section: Nadph Oxidase and Mhc-ii Antigen Presentationmentioning
confidence: 99%